MANAJEMEN PEMASARAN : ANALISIS PERSEPSI KONSUMEN TERHADAP CITRA MEREK PADA PRODUK LOKAL : PAKAIAN - Dimas Galih Saputra; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to analyze consumer perceptions of the brand image of fashion products from local brands in Indonesia. A qualitative approach was used with an in-depth interview method involving 15 informants, consisting of consumers aged 18-35 years who are active users of local fashion products. The research results show that consumer perceptions of local brands are influenced by several main factors, namely product quality, brand identity, and brand involvement in social and environmental communities. A positive brand image is formed when consumers experience consistent quality, innovative design, and the brand's commitment to local values ​​and sustainability. This research provides new insights into how local fashion brands can strengthen their position in the market by building an authentic and relevant image in the eyes of consumers.